Naphthalene diimide-based small molecule acceptors for fullerene-free organic solar cells. (1st July 2017) - Sung, Min Jae; Huang, Minjuan; Moon, Sang Hun; Lee, Tack Ho; Park, Song Yi; Kim, Jin Young; Kwon, Soon-Ki; Choi, Hyosung; Kim, Yun-Hi
Highlights: We synthesized new class of NDI-based small molecule acceptors. NDI-based small molecule acceptors have many advantages including high electron affinity and electron mobility, and well-matched energy levels with polymer donors. The device with NDI-TR had the highest FF and PCE among fullerene-free organic solar cells with NDI small molecule acceptors. Improved charge transport and minimized bimolecular recombination by smooth surface roughness and pronounced face-on orientation of polymer backbones resulted in high device efficiency. Abstract: Non-fullerene acceptors have attracted great attention as an alternative to fullerene derivatives to overcome their disadvantages such as limited molecular design due to fullerene moiety, electronic tuning via structural modification, and weak absorption in the visible range. In this work, we design a new class of naphthalenediimide (NDI)-based small molecule acceptors by introducing an NDI central core unit and A-D-A-D-A-type moiety. The NDI-TR is a promising material as an electron acceptor for OSCs because of many advantages including high electron affinity and electron mobility, and well-matched energy levels with polymer donors. The device based on NDI-TR had the highest fill factor (0.69) and power conversion efficiency (3.07%) among fullerene-free organic solar cells with NDI small molecule acceptors. This high device efficiency may be attributed to improved charge transport and minimized bimolecular recombination due to the smooth surface roughness and pronounced face-on orientation of polymer backbones in the bulk heterojunction film.